Short-Chain Fatty Acids Promote Intracellular Bactericidal Activity in Head Kidney Macrophages From Turbot (Scophthalmus maximus L.) via Hypoxia Inducible Factor-1α - Zhang, Jinjin; Zhang, Hui; Liu, Miao; Lan, Yawen; Sun, Huiyuan; Mai, Kangsen; Wan, Min (Frontiers in Immunology, 2020)
Short-chain fatty acids (SCFAs) are mainly produced by microbiota through the fermentation of carbohydrates in the intestine. Acetate, propionate and butyrate are the most abundant SCFA metabolites, and have been shown to be important in the maintenance of host health. In this study, head kidney macrophages (HKMs) were isolated and cultured from turbots. We found that the antibacterial activity of HKMs was increased after these cells were incubated with sodium butyrate, sodium propionate or sodium acetate. Interestingly, our results showed that all three SCFAs enhanced the expression of hypoxia inducible factor-1 α (HIF-1α) in HKMs, and further study confirmed that butyrate augmented the oxygen consumption of these cells. Moreover, HIF-1α inhibition diminished the butyrate-promoted intracellular bacterial killing activity of macrophages, and SCFAs also raised the gene expression and activity of lysozymes in HKMs via HIF-1α signaling. In addition, our results suggested that butyrate induced HIF-1α expression and the bactericidal activity of HKMs through histone deacetylase inhibition, while G protein-coupled receptors did not contribute to this effect. Finally, we demonstrated that butyrate induced a similar response in the murine macrophage cell line RAW264.7. In conclusion, our results demonstrated that SCFAs promoted HIF-1α expression via histone deacetylase inhibition, leading to the enhanced production of antibacterial effectors and increased bacterial killing of macrophages.